The Impact of Profitability and Liquidity on Earnings Growth: Evidence from Food and Beverage Firms Listed on the IDX - Lumbangaol, Herawati; Samosir, Hendrik; Sinurat, Mangasa (Manunggal Halim Jaya, 2025)
This study examines the effect of profitability and liquidity on earnings growth in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The research uses secondary data derived from the companies' annual financial reports. A purposive sampling method was employed, resulting in a sample of 30 companies that met the predefined criteria. Data analysis was conducted using multiple linear regression with SPSS version 25, descriptive statistics, normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. Hypothesis testing was carried out using the t-test and F-test at a significant level of 0.05. The findings show that profitability (Net Profit Margin) has a positive but insignificant effect on earnings growth. Meanwhile, liquidity (Cash Ratio) has a negative and insignificant effect on earnings growth. Simultaneously, neither profitability nor liquidity significantly influences earnings growth.